PSYCHOLOGICAL RESILIENCE OF TOURISM WORKERS: THE CASE OF ANTALYA - Birgül Aydın; Emre Ozan Aksöz; Esin Yücel (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Psychological resilience is the state of being able to exhibit the demanded/expected positive behaviour when the individual is faced with difficulties. In the tourism sector where intensive labour is involved, the psychological resilience of the employees who provide the service directly to the customer against the intensive working conditions remains crucial. The aim of this study is to determine whether psychological resilience levels of accommodation workers differ according to demographic characteristics and job characteristics. The population of the research consists of the employees of five-star hotel businesses in Antalya. In the research, two-part questionnaire was used to determine the individual characteristics of the employees and psychological resilience scale for adults (PRSA). For the evaluations made on 570 questionnaires, percentage and frequency analysis, t test, Anova tests were applied. As a result of the analysis, it was concluded that perceptions of marital status, sector experience, status, education level and income level were determinant on psychological resilience levels of employees. The contribution of this paper is that understanding the psychological state of the personnel working in tourism sector. Thereby, it will be possible to understand the importance of the human factor in tourism as a labor-intensive sector.